Peranan Kepala Sekolah Dalam Meningkatkan Mutu Dan Kompetensi Guru Agama Hindu Di Sekolah Dasar - Nurmawati, Ni Kadek Yeni; Madra, I Wayan (LPM IHDN Denpasar, 2018)
The era of globalization has an impact on the emergence of intense competition in various sectors such as; in the field of science and technology, economics and others. Competition in maintaining or competing for various sectors requires the existence of competent human beings in order to continue to exist in the midst of socio-cultural changes and the rapid development of science and technology. Speaking of the quality of education, the education component is certainly a central point which will affect the quality of education produced. One component of education in question is the existence of teachers or educators.Principals play an important role in increasing teacher motivation and competence in schools. The failure of school principals to create effective and efficient learning conditions will have an impact on the future of students, often educators are also used as